Frequency of Hypertension in Pregnant Women Visiting District Head Quarter Hospital Rajanpur, Pakistan (Medical Forum Monthly, 2024)
Objective: To determine the prevalence of hypertension in pregnant ladies throughout the pregnancy period.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Medical Clinic DHQ Rajanpur from 1st June to 15th July 2016.Materials and Methods: 100 pregnant women with gestational age from 20 weeks ahead were contained. Gestational age was determined by ultrasound and from the concluding menstrual period. Pregnancy-induced hypertension was determined by measuring the blood pressure and based on clinical examination. The data was registered in a pre-designed table, entered and analyzed by using SPSS 22.Results: Our study found that 57% of pregnant women who visited the hospital clinic were found with hypertension. The average age of the respondents was ± 31.54 and Standard Deviation of 3.18. Most of the respondents about (64.5%) were form the middle-aged group (26-35 years old), the highest age of childbearing.Conclusion: Pregnancy is associated with a complex threat of pregnancy-induced hypertension. The mothers experience most of the complications during pregnancy and childbirth. Early booking, good care throughout pregnancy and childbirth and the rational use of contraceptive services can prevent complications from occurring.